SHARIA TOURISM DEVELOPMENT STRATEGY IN NATURAL RECREATION SITES OF BATU CITY, EAST JAVA - Azzah Fauziyah Cholis; Luchman Hakim; Edriana Pangestuti (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
Batu city has abundance natural recreation sites, in which many of them has been visited by tourist. With the recent development of sharia-based tourism industry, there are opportunities for Batu to develop sharia based tourism in Batu, especially in natural recreation sites. The purpose of this research is to identify the implementation of sharia value in natural recreatin sites and Sharia Tourism development strategy in the area of Natural Tourism Batu City. Data were obtained from questionnaires given to 84 respondents consisting of visitors, tourism employees, tour manager, and policymaker then being analyzed for the implementation of sharia tourism and strategy on the development of natural tourism. SWOT strategy was used to determine every aspect of tourism development (weight 0.00 to 1.00). The results of the analysis with SWOT quadrant shows that implementation most of it has been applied. While sharia development strategy in nature tourism of Batu city is at the quadrant I which is Aggressive strategy. The Alternative strategy that used is SO strategy (Strengths-Opportunities) which includes: 1. Improving the quality of service that will lead to the system of sharia tourism; 2. Utilizing all resources as a attraction of sharia tourism; 3. Involving all the stakeholders in cooperation planning and management of natural tourism principled sharia;and 4. Improving foreign language skills to all Employees and management of tourism.